2017
DOI: 10.3835/plantgenome2016.07.0070
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genomic Estimated Breeding Values Results in Rapid Genetic Gains for Drought Tolerance in Maize

Abstract: More than 80% of the 19 million ha of maize (Zea mays L.) in tropical Asia is rainfed and prone to drought. The breeding methods for improving drought tolerance (DT), including genomic selection (GS), are geared to increase the frequency of favorable alleles. Two biparental populations (CIMMYTAsia Population 1 [CAP1] and CAP2) were generated by crossing elite Asian-adapted yellow inbreds (CML470 and VL1012767) with an African white drought-tolerant line, CML444. Marker effects of polymorphic single-nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…Using recombinant inbred lines derived from a cross between B73 and Mo17, Massman et al ( 2013 ) showed that GS produced from 14 to 50% higher genetic gains for stover and grain yield than marker assisted recurrent selection for several traits in a maize biparental population. This result was then verified in tropical maize (Beyene et al, 2015 ; Vivek et al, 2017 ). Beyene et al ( 2015 ) found that the average genetic gain per year across eight tropical maize populations of GS was three times higher than that of pedigree based phenotypic selection in drought stress conditions.…”
Section: Introductionmentioning
confidence: 73%
“…Using recombinant inbred lines derived from a cross between B73 and Mo17, Massman et al ( 2013 ) showed that GS produced from 14 to 50% higher genetic gains for stover and grain yield than marker assisted recurrent selection for several traits in a maize biparental population. This result was then verified in tropical maize (Beyene et al, 2015 ; Vivek et al, 2017 ). Beyene et al ( 2015 ) found that the average genetic gain per year across eight tropical maize populations of GS was three times higher than that of pedigree based phenotypic selection in drought stress conditions.…”
Section: Introductionmentioning
confidence: 73%
“…Another example of genetic gains from rapid-cycle GS on CIMMYT maize is two biparental maize populations (F 2:3 ) from Asia (CAP1 and CAP2) that were developed and evaluated for testcross performance under drought and optimal conditions [72]. The genetic gains per year for PS versus GS in drought environments were 0.067 t/ha versus 0.124 t/ha, respectively, for CAP1, and 0.076 t/ha versus 0.104 t/ha, respectively, for CAP2.…”
Section: Genetic Gains From Rapid Selection Cycle Gs: Cimmyt Maize Bimentioning
confidence: 99%
“…In another study, negative GEBV for yield were observed for synthetic hexaploid spring bread wheat lines evaluated across heat and irrigated environments [36]. Selection for drought tolerance in maize using GEBV, in contrast, has resulted in rapid genetic gains and positive selection responses through using molecular markers associated with yield under drought stress [37]. While selecting lines based on GEBV alone should be considered with caution, the implementation of genomic selection in breeding programs should help increase the rate of genetic gains through a faster breeding cycle, higher selection intensity, and efficiency of genomic prediction approaches in integrating novel genetic material in wide-crosses and pre-breeding programs [38].…”
Section: Discussionmentioning
confidence: 99%